DETERMINATION OF MEASUREMENT ERROR OF ELECTRICAL ENERGY QUALITY INDICATORS BY THE CORRELATION METHOD - FILONENKO, Sergii; LARIN, Vitaliy; STAKHOVA, Anzhelika (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The problem of energy conservation is urgent not only for Ukraine but for the whole world. One of the main causes of non-productive energy costs in the energy sector is high losses in power grids. The problem of electricity quality is the focus of many researchers and practitioners of energy and electrification. The co-supply of single-phase and three-phase electrical energy receivers from a three-phase four-wire network is widespread in the power supply systems of industrial enterprises. In such cases, there is almost always a phase asymmetry of the load, as well as significant currents in the zero wire. These factors lead to a decrease in the quality of the voltage and are the cause of economic damage. Organization of hardware control of electricity quality indicators, organizational and economic mechanism of influence on the cause of deterioration of electricity quality, development of methods and technical methods of distortion are important for normalization of electricity quality. The error of the correlation method for measuring the unbalanced voltage of a three-phase network based on the preliminary conversion of a three-phase voltage to a two-phase voltage with subsequent decomposition into orthogonal components using a discrete Fourier transform is estimated.